(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The essay analyzes the implementation of the principle of secularism in the national health system, focusing on three themes: religious assistance services provided in health facilities, the issue of male ritual circumcisions and the conscientious objection for healthcare professionals. The analysis carried out by the author shows that to identify how the health administration must respond to the needs for the protection of freedom of conscience and religion, which emerge in contemporary society, it is necessary to relate the principle of secularism with the other fundamental principles of public services.